Kaidah Fiqih Siyasah Berhubungan dengan Perubahan hukum تَغَيُّرُ الْفَتْوَى بِتَغَيُّرِ الْأَزْمَانِ وَالْأَحْوَالِ لا ينكر تغير الأحكام بتغير الأزمان والأمكان - Nimas Ifthinatun Nabila; Audy Agustina Singgih Putri; M. Wildan Qolbi Habibi; Nuris Hari Pramadana; Muh. Zamroni (Jurnal Kajian Islam dan Sosial Keagamaan, 2025)
The fiqh siyasah principles " تَغَيُّرُ الْفَتْوَى بِتَغَيُّرِ الْأَزْمَانِ وَالْأَحْوَالِ " and " لا ينكر تغير الأحكام بتغير الأزمان والأمكان" state that Islamic law can change in accordance with the developments of time, place, and circumstances. Fatwas in Islam are dynamic as they respond to the evolving needs of society. Historically, changes in fatwas were made by Imam al-Shafi’i when he moved from Iraq to Egypt, highlighting the importance of social context in legal rulings. These principles indicate that ijtihad is essential for addressing new issues that are not explicitly discussed in the texts. However, such changes do not apply to definitive (qath’i) rulings, such as the obligation of prayer or the prohibition of adultery. Therefore, Islamic law possesses flexibility within the realm of ijtihadiyyah, allowing it to remain relevant and contextual in the lives of Muslims.